Multi-center investigation of the clinical and pathological characteristics of inflammatory breast cancer based on Chinese Society of Breast Surgery (CSBrs-007) - Qi Zhou; Hai-Ping Zhang; Ya-Ting Zhao; Xiao-Hong Wang; Wei Xiong; Yun-Jiang Liu; Jing-Hua Zhang; Qiang Shi; Chinese Society of Breast Surgery (Chinese Medical Journal, 2020)
Abstract. Background. Inflammatory breast cancer (IBC) is an aggressive type of cancer with poor prognosis and outcomes. This study aimed to investigate clinicopathological features, molecular characteristics, and treatments among Chinese patients diagnosed with IBC. Methods. We collected data of 95 patients with IBC who were treated by members of the Chinese Society of Breast Surgery, from January 2017 to December 2018. The data, including demographic characteristics, pathological findings, surgical methods, systemic treatment plans, and follow-up, were obtained using a uniform electronic questionnaire. The clinicopathological features of different molecular types in patients without distant metastases were compared using the Kruskal-Wallis (H) test followed by post hoc analyses. Results. Lymph node metastasis was noted in 75.8% of all patients, while distant metastasis was noted in 21.4%. Pathological findings indicated invasive ductal and lobular carcinomas in 86.8% and 5.3% of cases, respectively. Hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) (41.5%) and HR−/HER2+ (20.1%) were the most common biologic subtypes, followed by HR+/HER2+ (19.1%) and HR−/HER2− (19.1%). Stage III IBC was treated via pre-operative neoadjuvant chemotherapy in 87.7% of the cases, predominantly using anthracycline and taxanes. A total of 91.9% of patients underwent surgical treatment. Among them, 77.0% of the patients underwent modified radical mastectomy, 8.1% of whom also underwent immediate breast reconstruction. The Kruskal-Wallis test revealed that the efficacy of chemotherapy significantly differed among those with HR+/HER2− and HR−/HER2− tumors (adjusted P = 0.008), and Ki-67 expression significantly differed in HR−/HER2+ and HR+/HER2+ molecular subtypes (adjusted P = 0.008). Conclusion. Our study provides novel insight into clinicopathological characteristics and treatment status among patients with IBC in China, and might provide a direction and basis for further studies. Trial registration. chictr.org.cn, No. ChiCTR1900027179; http://www.chictr.org.cn/showprojen.aspx?proj=45030